A Self‐Sodiophilic Carbon Host Promotes the Cyclability of Sodium Anode. (6th December 2020) - Tao, Lei; Hu, Anyang; Mu, Linqin; Kautz, David J.; Xu, Zhengrui; Feng, Yiming; Huang, Haibo; Lin, Feng
Abstract: Benefiting from abundant resource reserves and considerable theoretical capacity, sodium (Na) metal is a strong anode candidate for low‐cost, large‐scale energy storage applications. However, extensive volume change and mossy/dendritic growth during Na electrodeposition have impeded the practical application of Na metal batteries. Herein, a self‐sodiophilic carbon host, lignin‐derived carbon nanofiber (LCNF), is reported to accommodate Na metal through an infiltration method. Na metal is completely encapsulated in the 3D space of the LCNF host, where the strong interaction between LCNF and Na metal is mediated by the self‐sodiophilic sites. The resulting LCNF@Na electrode delivers good cycling stability with a low voltage hysteresis and a dendrite‐free morphology in commercial carbonate‐based electrolytes. When interfaced with O3‐NaNi0.33 Mn0.33 Fe0.33 O2 and P2‐Na0.7 Ni0.33 Mn0.55 Fe0.1 Ti0.02 O2 cathodes in full cell Na metal batteries, the LCNF@Na electrode enables high capacity retentions, long cycle life, and good rate capability. Even in a "lean" Na anode environment, the full cells can still deliver good electrochemical performance. The overall stable battery performance, based on a self‐sodiophilic, biomass‐derived carbon host, illuminates a promising path towards enabling low‐cost Na metal batteries. Abstract : A self‐sodiophilic carbon host, lignin‐derived carbon nanofiber (LCNF), is designed to promote the cyclability of a dendrite‐free sodium (Na) anode. Benefiting from the continuous interlayer cavities and self‐sodiophilic sites in the 3D space, Na metal is completely encapsulated in the 3D space of the LCNF host, which offers good rate capability and improves cycling stability in Na metal batteries.